Sprektrum Perencanaan Pembangunan dalam Pengentasan Kemiskinan oleh Pemerintah Desa - Dhanny Septimawan Sutopo; Dania Nur Shabrina (Jurnal Sosiologi Andalas, 2022)
Abstract This research aims to find out the poverty alleviation conducted by the village government through the implementation of development planning in Ngroto Village. The village government has an obligation to carry out its duties in carrying out village development which is then listed in the Village Medium Term Development Planning (RPJM Desa). Ngroto Village, Pujon Subdistrict, Malang Regency is one of the villages that has problems at a high poverty level, namely in 2011 reached 477 Family Cards (KK) based on BPS Malang Regency. However, currently poverty has been successfully eradicated by the village government as evidenced by the number of poor people who are only 27 families. This research was compiled using qualitative research method with intrinsic case study approach. The results of this study show that the efforts of the Ngroto Village Government in improving the accessibility and capabilities of the community are the main factors so that poverty alleviation can be successful. In addition, in the process of implementing or preparing development planning, the Ngroto Village Government prioritizes collaborative and participatory aspects with the community so that the development carried out can be on target.